Pengaruh Keahlian, Pengalaman Audit, dan Pengetahuan Akuntansi dan Auditing terhadap Ketepatan Pemberian Opini Audit - Devina Mahmuda; Putri Nurmala (Jurnal Pasar Modal dan Bisnis, 2020)
This study aims to obtain empirical evidence regarding the effect of expertise on the accuracy of giving audit opinions, audit experience on the accuracy of giving audit opinions, and knowledge of accounting and auditing on the accuracy of giving an audit opinion. For this reason, research was carried out on the hood of the city of Depok. The population in this study were auditors who worked on the hood of the city of Depok. This study used convenience sampling. Data were collected through a questionnaire, which was distributed to the sample. The data analysis technique used is multiple regression analysis and hypothesis testing t test to see the effect partially. The results showed that expertise had a significant positive effect on the accuracy of giving audit opinions, audit experience did not have a significant effect on the accuracy of giving audit opinions, and accounting and auditing knowledge had a significant positive effect on the accuracy of giving an audit opinion.